Evaluation of the impact of engineered nanoparticles on the operation of wastewater treatment plant - Eduok, Samuel (Cranfield University, 2013)
The effect of engineered nanoparticles (ENPs) mixture consisting of silver oxide, (Agg0[Silver Oxide Nanopartical], 20 nm), titanium dioxide, (TiO2[Titanium dioxide], 30-40 nm) and zinc oxide, (ZnO, 20 nm) compared with their bulk metal salts was evaluated against unspiked activated sludge (control) using 3 parallel pilot-scale treatment plants. The total concentration of the ionic species of Ag+ Ti[Silver + Titanium] and Zn(2+) in the effluent of the ENP spiked activated sludge (AS) was below limits of detection and> 99% of the spiked ENP were found in the waste activated sludge (WAS), whereas 39 – 58 % of Ag0[Silver Oxide Nanopartical], 51 – 63 % and 58 – 74 % of ZnO ion concentrations were recovered in the anaerobic digestate (AD) cake suggesting higher affinity of ENPs to WAS than to anaerobic digestate. ENPs induced a 2-fold increase of the microbial community specific oxygen uptake rate (SOUR) compared with the control and > 98 % of ammonia and 80 % of COD were removed from the AS suggesting that the heterotrophic biomass retained their ability to nitrify and degrade organic matter at the spiked ENP concentration. The floc size and cultivable microbial abundance was reduced in the ENP spiked AS with no apparent disruption of the overall AS process efficiency. However, scanning electron microscopic analysis clearly showed damage to specific microbial cells. The lipid fingerprint and 16S rRNA gene-based pyrosequencing evidenced the dominance of Proteobacteria, Firmicutes, and Bacteriodetes with a clear temporal shift in microbial community structure. The prominent nano-tolerant bacterial species identified were Acidovorax, Rhodoferax, and Comamonas whereas Methanocorpusculum and Methanosarcina were recovered in AS and were the dominant Archaea in the AD with 99 and 98 % similarities to the closest culturable relative. Their presence in the AS suggests tolerance to ENPs and oxygen-dependent respiration. V. fisheri activity was not sensitive to the ionic concentrations of the ENP or metal salt mixture in the digestate samples and illustrates the need to develop bioassay using indigenous wastewater microorganisms to detect the potential effect of ENP. Overall, unlike other xenobiotic compounds, ENPs can hasten the natural selection of microbial species in activated sludge and anaerobic digestion processes.
Keywords: Activated sludge; anaerobic digestion; engineered nanoparticles; metal salts; Bacteria; Archaea; potential effect; contaminant removal